Klassen Typology and Williamson Index to Measure Macroeconomics in South Sulawesi Province - Elpisah, E.; Suarlin, S.; Yahya, Muhammad (Golden Ratio of Social Science and Education, 2021)
This study was conducted to analyze the classification of economic growth of each district/city in South Sulawesi Province use Klassen typology, Williamson index, and logistic regression. Analyze income inequality between districts/cities in South Sulawesi Province. This study uses secondary data with a sample of fifteen years from 2005 to 2019. The results of the study show that: (1) several districts/cities have potential as developed and fast-growing areas, developed but depressed areas, fast-developing areas, and relatively underdeveloped areas; (2) income inequality in South Sulawesi Province is in a low condition; (3) economic growth and income disparity have a negative and significant effect on welfare in South Sulawesi Province. This means that economic growth and growth disparities affect the community's welfare in South Sulawesi Province. Economic development results do not only indicate the direction of achieving specific economic growth rates. Based on the results, it can be concluded that the economic growth has fluctuated. The Williamson Index shows that there are disparities. Partially, economic growth and income disparity significantly affect people's welfare in South Sulawesi Province. So that, the local government in its program is also expected to be able to more intensively carry out efforts to equalize income distribution social welfare.